Enhanced photocatalytic and electrochemical properties of green synthesized strontium doped titanium dioxide nanoparticles for dye removal and supercapacitor applications - Yonas Etafa Tasisa; M. Gunasekaran; Tridib Kumar Sarma; Ramaswamy Krishnaraj; M. Arivanandhan (Scientific Reports)
Abstract The development of multifunctional nanomaterials for environmental remediation and energy storage is critical for sustainable technologies. In this study, we synthesized strontium-doped titanium dioxide (Sr-TiO2) nanoparticles (NPs) via a green method and investigated their structural, optical, and electrochemical properties to enhance photocatalytic and supercapacitive performance. Characterization results confirmed successful Sr incorporation into the TiO2 lattice. X-ray diffraction (XRD) analysis revealed a slight shift in peak positions, indicating lattice distortion due to Sr doping. Scanning electron microscopy (SEM) showed uniform, well-dispersed nanoparticles, while energy-dispersive X-ray (EDX) spectra confirmed elemental composition. UV-visible spectroscopy (UV-Vis) demonstrated a redshift in absorption, reducing the bandgap and enhancing visible-light absorption. Fourier transform infrared (FTIR) spectroscopy identified characteristic functional groups, and Brunauer–Emmett–Teller (BET) analysis indicated increased surface area, favoring photocatalytic and electrochemical activity. The photocatalytic performance of Sr-TiO2 NPs was assessed through Methylene Orange (MO) and Congo Red (Con-R) degradation under visible light at different pH levels. Under optimized conditions, Sr-TiO2 NPs achieved 94.48% MO removal in 100 min and 97.89% Con-R removal in 70 min, following pseudo-first-order kinetics, demonstrating their efficiency as visible-light-driven photocatalysts for wastewater treatment. Electrochemical studies, including cyclic voltammetry (CV), charge-discharge tests, and electrochemical impedance spectroscopy (EIS), revealed improved charge storage and lower charge transfer resistance compared to bare TiO2. The Sr-TiO2 NPs exhibited enhanced specific capacitance and good electrochemical stability, underscoring their potential as high-performance electrode materials for supercapacitors. These findings highlight a sustainable approach to environmental remediation and energy storage by leveraging Sr-doped TiO2 nanomaterials for dual-functional applications.